2013
DOI: 10.1039/c3sm51824h
|View full text |Cite
|
Sign up to set email alerts
|

Versatile tuning of supramolecular hydrogels through metal complexation of oxidation-resistant catechol-inspired ligands

Abstract: The mussel byssal cuticle employs DOPA-Fe3+ complexation to provide strong, yet reversible crosslinking. Synthetic constructs employing this design motif based on catechol units are plagued by oxidation-driven degradation of the catechol units and the requirement for highly alkaline pH conditions leading to decreased performance and loss of supramolecular properties. Herein, a platform based on a 4-arm poly(ethylene glycol) hydrogel system is used to explore the utility of DOPA analogues such as the parent cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
160
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 150 publications
(169 citation statements)
references
References 48 publications
7
160
0
2
Order By: Relevance
“…The importance of redox for balancing the adhesion and cohesion of mussel mimetic adhesive polypeptides has been recognized for many years (e.g. Yu and Deming, 1998), but countermeasures to regulate the reactivity of catechol-functionalized synthetic polymers have only recently taken hold (Menyo et al, 2013;Holten-Andersen et al, 2011;Heo et al, 2012;Krogsgaard et al, 2015;Sedó et al, 2012). Understanding how a reducing interface is sustained between the plaque and substratum will be key to developing the best technologies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of redox for balancing the adhesion and cohesion of mussel mimetic adhesive polypeptides has been recognized for many years (e.g. Yu and Deming, 1998), but countermeasures to regulate the reactivity of catechol-functionalized synthetic polymers have only recently taken hold (Menyo et al, 2013;Holten-Andersen et al, 2011;Heo et al, 2012;Krogsgaard et al, 2015;Sedó et al, 2012). Understanding how a reducing interface is sustained between the plaque and substratum will be key to developing the best technologies.…”
Section: Resultsmentioning
confidence: 99%
“…6B) has three distinct pH-dependent steps known as mono, bis and tris that have been simulated (Xu, 2013); these refer to the ligand:metal stoichiometry (Taylor et al, 1996). The mono-Fe 3+ form predominates at acidic pH, and cross-linking bis and tris forms with Fe 3+ typically require pH >7, although the precise pH at which Dopa transitions from mono to bis to tris depends on the pK a of the phenolic hydroxyls (Menyo et al, 2013;Taylor et al, 1996); in Dopa-proteins, this is likely to depend on local sequence. The neutral imidazole of histidine provides a suitable ligand for coordinative pH-dependent cross-linking and, in preCOLs, is typically associated with Cu 2+ or Zn 2+ ions (Harrington and Waite, 2007;Schmitt et al, 2015).…”
Section: Plaque Cohesion In Seawatermentioning
confidence: 99%
“…Notwithstanding this, the selfmending adhesion and cohesion of isolated dopa (3,4-dihydroxyphenyl-L-alanine)-containing adhesive proteins were shown to rely critically on maintaining dopa in an acidic and reducing environment 13,14 . Significantly different conditions are required to recapitulate the self-healing cohesion of tris-dopa-Fe 3+ -mediated complexes in proteins and polymers [7][8][9]15 . Such results increasingly suggest the importance of dopa, but also its subtle and diverse interfacial reactivity vis-à-vis the traditional and still widely held view that dopa, and catechols generally, function primarily as crosslinkers after their 2-electron oxidation to quinones 16 .…”
mentioning
confidence: 99%
“…Recently, some significant work has focused on non-covalent hydrogels, which are cross-linked by reversible interactions based on metal-ligand coordination in the polymer chains; these can provide stimuli responsiveness, magnetic self-healing and good mechanical properties [8][9][10][15][16][17][18][19][20]. Because of the thermodynamics and kinetic properties of metal-ligand coordination bonds, metal-ligand interactions can provide stable, reversible crosslinking points between polymers [21]. Recently, some researchers reported mussel-inspired stimuli responsive and self-healing hydrogels containing dynamic metal (Fe 3+ )-catechol interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some researchers reported mussel-inspired stimuli responsive and self-healing hydrogels containing dynamic metal (Fe 3+ )-catechol interactions. The hydrogels are pH-sensitive, i.e., the Fe 3+ mono-catecholate, bis-catecholate, or tris-catecholate complexes are formed when the pH is increased to a specified pH [21,[22][23][24][25]. Krogsgaard et al [9] reported a self-healing multi-responsive system by incorporating additional features of the mussel adhesive proteins for drug delivery platforms.…”
Section: Introductionmentioning
confidence: 99%